Analysis of Tax Amnesty Policy in Enhancing Economic Resilience - Cunayah, Cucun; Saputro, Guntur Eko; Murtiana, Sri (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze the contribution of the tax amnesty policy in Indonesia to strengthening economic resilience, focusing on two implementation periods: the 2016–2017 tax amnesty program and the 2022 voluntary disclosure program. It employs a qualitative approach using the library research method, examining secondary data from journal articles, government reports, and policy documents. The findings indicate that the implementation of the 2016-2017 tax amnesty program generated revenues of IDR 135 trillion, while the 2022 voluntary disclosure program contributed IDR 61 trillion. In the short term, the tax amnesty program helped increase tax revenues from previously non-compliant taxpayers and encouraged the repatriation of overseas assets. More importantly, the policy laid the foundation for a more comprehensive and credible national tax database. Although it received both support and criticism regarding its long-term effectiveness and the potential for moral hazard, the policy has demonstrated a partial contribution to fiscal space and revenue capacity, which are key components of economic resilience. These findings suggest that future tax reforms should strike a balance between fiscal incentives and stronger enforcement of tax compliance.